2018
DOI: 10.3390/su10124575
|View full text |Cite
|
Sign up to set email alerts
|

Future Impacts of Climate Change and Land Use on Multiple Ecosystem Services in a Rapidly Urbanizing Agricultural Basin, China

Abstract: Ecosystem services (ESs) in rapidly urbanizing agricultural basins are vulnerable to environmental changes. Adequately understanding the driving forces and the dynamics of ESs related to water quantity and quality can provide a basis for making sound management decisions on the development of basins. Here, we explored the impacts of future land use and climate changes on four ESs: nitrogen and phosphorous purification, water supply, and soil retention services in the Taihu Basin region of eastern China. Spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Ecosystem services are closely related to topography, land use, soil, biology, climate, and socio-economic factors [4]. Land use and climate change are considered to be the main driving forces of changes in ecosystem services [5,6]. Climate change determines the spatial and temporal distribution of ecosystem services, while land use change affects ecosystem services by changing the ecosystem structure and function [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ecosystem services are closely related to topography, land use, soil, biology, climate, and socio-economic factors [4]. Land use and climate change are considered to be the main driving forces of changes in ecosystem services [5,6]. Climate change determines the spatial and temporal distribution of ecosystem services, while land use change affects ecosystem services by changing the ecosystem structure and function [7].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that climate change was important factor affecting ESV [28][29][30]. The above researches can draw preliminary qualitative or quantitative conclusions that meteorological factors have influence on ESV.…”
Section: Discussionmentioning
confidence: 95%
“…Currently, research concerning the driving factors of ESV changes are plentiful [ 37 , 38 , 39 , 40 , 41 ], while direct drivers, such as land use change, and the application of new technologies attracts more attention [ 42 , 43 ]. For example, Liu et al [ 44 ] superimposed the impact of future climate scenarios and land use change on ESs to explore the overall effect of the changes on ESs. During the period of rapid economic development, population growth, economic development, and urban expansion have exerted unprecedented pressures and negative effects on the regional ESs [ 39 ], and the impact of national policies on the ESs should not be neglected, such as the Grain for Green Program [ 17 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%